Prescription for antibiotics at drug shops and strategies to improve quality of care and patient safety: a cross-sectional survey in the private sector in Uganda. Issue 3 (15th March 2016) - Mbonye, Anthony K; Buregyeya, Esther; Rutebemberwa, Elizeus; Clarke, Siân E; Lal, Sham; Hansen, Kristian S; Magnussen, Pascal; LaRussa, Philip
Abstract : Objectives: The main objective of this study was to assess practices of antibiotic prescription at registered drug shops with a focus on upper respiratory tract infections among children in order to provide data for policy discussions aimed at improving quality of care and patient safety in the private health sector in Uganda. Methods: A survey was conducted within 57 parishes from August to October 2014 in Mukono District, Uganda. Data was captured on the following variables: drug shop characteristics, training of staff in management of pneumonia, availability of guidelines and basic equipment, available antibiotics, knowledge on treatment of pneumonia in children aged <5 years. The main study outcome was the proportion of private health facilities prescribing an antibiotic. Results: A total of 170 registered drug shops were surveyed between August and October 2014. The majority of drug shops, 93.5% were prescribing antibiotics, especially amoxicillin and trimethoprim-sulfamethoxazole (septrin). The professional qualification of a provider was significantly associated with this practice, p=0.04; where lower cadre staff (nursing assistants and enrolled nurses) overprescribed antibiotics. A third, 29.4% of drug shop providers reported that antibiotics were the first-line treatment for children with diarrhoea; yet the standard guideline is to give oral rehydration salts and zinc tablets. Only few providers, 8.2%, had training on antibiotics, with 10.6% on pneumonia case management. Further to this, 7.1% drug shops had WHO-Integrated Management of Childhood Illness guidelines, and a negligible proportion (<1%) had respiratory timers and baby weighing scales. Although the majority of providers, 82.4%, knew severe signs and symptoms of pneumonia, few, 17.6%, knew that amoxicillin was the first-line drug for treatment of pneumonia in children according to the guidelines. Conclusions: There is urgent need to regulate drug shop practices of prescribing and selling antibiotics, for the safety of patients seeking care at these outlets.